Changing library spaces: finding a place for print - Jilovsky, C.; Genoni, Paul (Victorian Association for Library Automation (VALA), 2008)
This paper considers the storage options for print collections in a digital environment. Recent changes to library space use in particular are reducing the space available for print storage and forcing libraries to look to other solutions, including print repositories. Repositories potentially produce benefits to the networks of libraries they serve; to individual libraries within the network, and to the communities of researchers that using those libraries. The paper emphasises the Australian situation, and the discussion encompasses the policy developments that are necessary to optimise the benefits of a fully implemented national print repository for Australia.